THE IMPACT OF TAXES ON INDIVIDUAL LONG-TERM SAVINGS DECISION - Dominik Tschinkl; Nathalie Weikert; Dirk Kiesewetter (Copernican Journal of Finance & Accounting, 2022)
This paper uses experimental methods to analyze how different forms of taxation influence the decision between immediate consumption and saving. The parameters are chosen in such a way that the treatments No Tax, Immediate Taxation and Deferred Taxation have identical net payoffs, which should induce the same decisionmaking patterns. However, we find that these expectations only apply to the treatments No Tax and Immediate Taxation. The participants in the Deferred Taxation treatment show a significantly weaker preference for saving which hints at a misperception of this form of taxation. This result also has political implications as many OECD countries try to incentivize voluntary saving for retirement through deferred taxation. In the experiment, however, this type of taxation leads to less saving than an economically equivalent immediate taxation of savings. Furthermore, the paper shows that individuals only partially recognize the advantages of immediate or deferred taxation compared to a classic income tax. While the periodic yield is tax exempt in systems of immediate or deferred taxation, it is taxable under a classical income tax. The latter should have a negative effect on saving decisions. However, these theoretical predictions do not hold in our experiment.